Onion productivity in relation to irrigation water depths and nitrogen doses - Baptestini,Júlio Cezar M (2018)
ABSTRACT Onion is considered the third most important vegetable in terms of economic value in Brazilian horticulture. The factors of production which most limit the productivity of the species are water and nutrients; so, irrigation and soil fertility control are determinant criteria for crop success. The aim of this study was to evaluate the influence of different water depths and nitrogen doses on the productivity of onion, Aquarius hybrid. Five water depths [(0, 75, 100, 125 and 150% of crop evapotranspiration (ETc)] and five nitrogen doses (0, 120, 180, 240 and 300 kg ha-1, urea form), arranged in a scheme of subdivided plots, in a completely randomized design with four replicates. We used sprinkler irrigation system. Irrigation management and water depths were estimated using Irrigameter. Plants were harvested when more than 60% of them completed the vegetative period. The water depth corresponding to 150% of the crop evapotranspiration provided higher total and commercial onion productivities, applying doses of 226.8 and 229.8 kg ha-1 of nitrogen, respectively.